Strategi Penguatan Kolaborasi untuk Menghindari Polarisasi Sosial dalam Membangun Organisasi Inklusif di Kampung Bojong, Desa Bojongsari, Kecamatan Kedungwaringin, Kabupaten Bekasi - Raniasari Bimanti Esthi; Nur Azizah; Sopi Jaelani; Elisabet Simanjuntak; Sinar Mauliza Purnama (Lembaga Pengembangan Kinerja Dosen, 2025)
Social fragmentation within community organizations in Kampung Bojong, Bojongsari Village, Kedungwaringin Subdistrict, Bekasi Regency, has led to social polarization that hinders community cohesion and inclusive participation. This study aims to formulate strategies for strengthening collaboration to build inclusive and equitable organizations. The method used is a qualitative approach with a participatory case study design. Data was collected through participatory observation, in-depth interviews, and focused group discussions (FGDs), using purposive sampling techniques. Analysis was conducted thematically, and validity was ensured through triangulation and member checking. The results indicate that social polarization encompasses aspects of power, age, politics, economics, geography, and symbolism, reflected in exclusion, information inequality, and weak communication. Factors contributing to low collaboration include lack of trust, dominance of central figures, and limited member capacity. Interventions were implemented through a community-based action research model involving dialogue facilitation, collaborative training, and organizational strategy mentoring. Evaluations showed increased cross-group participation, the formation of communication forums, and reduced social tension. This study contributes practically and theoretically to building resilient organizations through participatory and transformative approaches.